STUDY OF DYNAMIC SORPTION OF OIL PRODUCTS IN WASTEWATER ON SORBENT (Multidisciplinary Journal of Science and Technology, 2026)
This article studies the dynamic sorption properties of composite sorbents obtained from local lignocellulose raw materials for the treatment of wastewater contaminated with petroleum products. The studies were conducted using a column method, and the adsorption efficiency, sorption capacity and regeneration properties of YP:KOH–10, AD:KOH–10 and YAD:KOH–10 sorbents for petroleum products were studied. The changes in the adsorption activity and outlet concentration of the sorbents over time during the dynamic sorption process were analyzed. Based on the results obtained, it was determined that the YAD:KOH–10 sorbent has the highest sorption capacity and adsorption efficiency. The results of the study showed that lignocellulose-based composite sorbents are promising adsorbent materials for the treatment of wastewater from petroleum products.